1981
DOI: 10.1038/291554a0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep and arousal on the processing of visual information in the cat

Abstract: Single units in the cat lateral geniculate nucleus and primary visual cortex show changes in both spontaneous and visually evoked firing as a function of the state of wakefulness. On arousal spontaneous firing is smoother and often reduced, whereas evoked responses are usually enhanced; the result is an increase in the signal-to-noise ratio. Single- and double-label 2-deoxyglucose autoradiographs show further that slow-wave sleep differentially depresses visually evoked activity in the deeper layers of the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
264
5
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(301 citation statements)
references
References 35 publications
23
264
5
2
Order By: Relevance
“…For example, stimulation of the reticular formation enhances responses and the signal to noise ratio in the visual cortex of the cat (Singer, 1979). The same effect can be observed after application of noradrenalin (Kasamatsu & Heggelund, 1982) or in awake cats in comparison to sleeping animals (Livingstone & Hubel, 1981). Gonzales-Lima and Scheich (1984a) demonstrated that combined acoustic and reticular stimulation leads to a higher of 2-DG labeling than pure acoustic stimulation in parts of the inferior colliculus of rats.…”
Section: Discussionmentioning
confidence: 61%
“…For example, stimulation of the reticular formation enhances responses and the signal to noise ratio in the visual cortex of the cat (Singer, 1979). The same effect can be observed after application of noradrenalin (Kasamatsu & Heggelund, 1982) or in awake cats in comparison to sleeping animals (Livingstone & Hubel, 1981). Gonzales-Lima and Scheich (1984a) demonstrated that combined acoustic and reticular stimulation leads to a higher of 2-DG labeling than pure acoustic stimulation in parts of the inferior colliculus of rats.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, the neocortical ACH concentration specifically increases during wakefulness and periods of sustained attention (1,2). Furthermore, iontophoresis of ACH in the neocortex of anesthetized animals (3)(4)(5) produces an increase in amplitude and signal-to-noise ratio (SNR) of evoked sensory responses similar to those occurring after transition from sleep to wakefulness (6). Conversely, experimental lesions of cholinergic neurons in the basal forebrain (7), the major source of neocortical ACH, or genetically induced reduction of ACH release (8) lead to impaired sensory processing.…”
mentioning
confidence: 99%
“…The burst state results from relative hyperpolarization and the tonic state from relative depolarization of the resting membrane potential (McCormick and Bal, 1997;Steriade et al, 1993). During EEG synchronized sleep when the thalamic neurons are hyperpolarized and in burst mode, there is a diminished responsiveness of thalamic sensory neurons to stimuli within their receptive fields with lowered signal-to-noise ratio (Livingstone and Hubel, 1981;McCormick and Feeser, 1990). The thalamic burst and tonic activity states are seen in thalamocortical relay and thalamic reticular nucleus neurons.…”
Section: Sleep-wake Systemsmentioning
confidence: 99%